Mutation in MPDZ causes severe congenital hydrocephalus. Issue 1 (13th December 2012) - Al-Dosari, Mohammed S; Al-Owain, Mohammed; Tulbah, Maha; Kurdi, Wesam; Adly, Nouran; Al-Hemidan, Amal; Masoodi, Tariq A; Albash, Buthainah; Alkuraya, Fowzan S
Abstract : Background: Congenital hydrocephalus is an important birth defect that is heterogeneous in aetiology and clinical presentation. Although genetics is believed to play an important role in the aetiology of non-syndromic congenital hydrocephalus, the overwhelming majority of cases lack mutations in L1CAM, the only disease gene identified to date. The purpose of this study is to identify a novel genetic cause of congenital hydrocephalus. Methods: Families with congenital hydrocephalus were phenotyped clinically and, in one family, autoyzogisty mapping and linkage analysis were pursued. Sequencing of the genes within the candidate locus was followed by targeted sequencing of the likely candidate gene in two other families. Results: We have identified a family in which severe congenital hydrocephalus of the communicating type follows an autosomal recessive mode of inheritance. Linkage analysis and autozygosity mapping narrowed the critical interval to 6.9 Mb on 9p24.1–p22.3 spanning just six genes. Direct sequencing of these genes revealed a truncating mutation in MPDZ, encoding a tight junction protein. Remarkably, we have also identified the same founder mutation in a stillbirth with massive congenital hydrocephalus from another family. Conclusions: Our data strongly support the candidacy of MPDZ as a novel congenital hydrocephalus disease gene.